2011
DOI: 10.1021/jf203096q
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition and Antioxidant Activity of Aqueous Infusions from Capparis spinosa L. and Crithmum maritimum L. before and after Submission to a Two-Step in Vitro Digestion Model

Abstract: This study investigated the phenolic composition and antioxidant activities of aqueous infusions from wild-grown caper (Capparis spinosa L.) and sea fennel (Crithmum maritimum L.) from the Dalmatia region (Croatia) before and after their submission to an in vitro digestion process. HPLC/UV-vis-DAD/ESI-MS analysis of the caper infusion identified rutin, kaempferol 3-O-rutinoside, and isorhamnetin 3-O-rutinoside as dominant flavonoids in the matrix together with a series of cinnamoylquinic acid derivatives, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 43 publications
17
113
1
1
Order By: Relevance
“…Further enhancement of biological functions in Capsicum annuum was observed when Ti ions were sprayed on leaves [43], therefore we decided to use this approach in our experiments. Siracusa et al [24] tested infusions from C. maritimum in gastrointestinal model. They found out that total polyphenol content and its antioxidant capacity decreased in digested samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further enhancement of biological functions in Capsicum annuum was observed when Ti ions were sprayed on leaves [43], therefore we decided to use this approach in our experiments. Siracusa et al [24] tested infusions from C. maritimum in gastrointestinal model. They found out that total polyphenol content and its antioxidant capacity decreased in digested samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, content of flavonoids, tannins, and also total polyphenols in the different parts of C. maritimum was evaluated and the presence of phenolic acids (PhAs), i.e., benzoic and cinnamic acid derivatives, qualitatively analyzed by HPLC [3,23]. In vitro digestion model of antioxidant capacity of aqueous infusions from wild-grown C. maritimum was studied and chlorogenic acid and its derivatives were the most important class of polyphenols found in those extracts [24]. Several plants containing PhAs are widely used in phytotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…with carbon tetrachloride (CCl 4 ) and paracetamol, and in vitro with thioacetamide and galactosemia. Siracusa et al (13) demonstrated that phenolic acid in Capparis spinosa has an antioxidant function. In a study by Bonina et al, antioxidant activity was reported due to flavonoids and hydroxycinnamic contained in Capparis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CSE extract was reported to be rich in flavonoids such as kaempferol, rutin, quercetin and quercetin derivatives, which are known to have anti-allergic, anti-inflammatory, antioxidant, anti-fungal, anti-bacterial anti-hepatotoxic, antidiabetic, antiproliferative and antitumor properties. Recently, the effect of plant extracts on melanogenesis has been reported and compounds, such as glycyrrhizin, quercetin and scoparone, were found to stimulate melanogenesis (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Antioxidant and Antitumor Activities Of Capparis Spinosa L mentioning
confidence: 99%